2017
DOI: 10.1038/cr.2017.85
|View full text |Cite
|
Sign up to set email alerts
|

Smad5 acts as an intracellular pH messenger and maintains bioenergetic homeostasis

Abstract: Both environmental cues and intracellular bioenergetic states profoundly affect intracellular pH (pHi). How a cell responds to pHi changes to maintain bioenergetic homeostasis remains elusive. Here we show that Smad5, a well-characterized downstream component of bone morphogenetic protein (BMP) signaling responds to pHi changes. Cold, basic or hypertonic conditions increase pHi, which in turn dissociates protons from the charged amino acid clusters within the MH1 domain of Smad5, prompting its relocation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…22212) ( Hockemeyer et al., 2009 ). AAVS1-LSLm1-GFP, AAVS1-LSLm2-GFP, AAVS1-LSLm3-GFP, and AAVS1-LSLm4-GFP were obtained by replacing the 5′ LoxP site within the AAVS1-LSL-GFP donor vector with the mutant LoxP sequence shown in Figure 5 A. gRNAs were constructed as described previously ( Fang et al., 2017 , Mali et al., 2013 ), and gRNA targeting sequences for PAX6 and FOXA2 are shown in Figure S1 . PAX6-P2A-Cre, FOXA2-P2A-Cre, PAX6-Cre ERT2 , and FOXA2-Cre ERT2 donor plasmids were constructed by ligating the left and right homologous arms with Cre or Cre ERT2 cassettes PCR amplified from pCAG-Cre-ERT2 (Addgene, no.…”
Section: Methodsmentioning
confidence: 99%
“…22212) ( Hockemeyer et al., 2009 ). AAVS1-LSLm1-GFP, AAVS1-LSLm2-GFP, AAVS1-LSLm3-GFP, and AAVS1-LSLm4-GFP were obtained by replacing the 5′ LoxP site within the AAVS1-LSL-GFP donor vector with the mutant LoxP sequence shown in Figure 5 A. gRNAs were constructed as described previously ( Fang et al., 2017 , Mali et al., 2013 ), and gRNA targeting sequences for PAX6 and FOXA2 are shown in Figure S1 . PAX6-P2A-Cre, FOXA2-P2A-Cre, PAX6-Cre ERT2 , and FOXA2-Cre ERT2 donor plasmids were constructed by ligating the left and right homologous arms with Cre or Cre ERT2 cassettes PCR amplified from pCAG-Cre-ERT2 (Addgene, no.…”
Section: Methodsmentioning
confidence: 99%
“…). More recently, histones, (see below), as well as Smad5, whose nuclear‐cytoplasmic translocation is regulated by direct proton binding, have also been proposed to serve as cellular sensors of acid‐base status, although additional work seems warranted before a functionally relevant role of these proteins in acid‐base‐sensing can be established.…”
Section: Signalling Mechanisms Linking Ph To Cell Proliferationmentioning
confidence: 99%
“…In addition to extracellular pH, pHi has been shown to control the subcellular localization of the transcriptional effector, Smad5 [ 58 ]. Fang and colleagues showed that alkalinized pHi induced cytoplasmic Smad5 accumulation and accelerated glycolytic flux whereas acidic pHi induced nuclear localization and expression of Smad5 target genes [ 58 ].…”
Section: Transcriptional Regulation and Phmentioning
confidence: 99%
“…In addition to extracellular pH, pHi has been shown to control the subcellular localization of the transcriptional effector, Smad5 [ 58 ]. Fang and colleagues showed that alkalinized pHi induced cytoplasmic Smad5 accumulation and accelerated glycolytic flux whereas acidic pHi induced nuclear localization and expression of Smad5 target genes [ 58 ]. Additionally, it was also shown that Smad5 plays a crucial role in maintaining the cellular bioenergetic homeostasis by regulating hexokinase 1 (HK1) [ 58 ], a rate-limiting enzyme in glycolysis [ 4 ].…”
Section: Transcriptional Regulation and Phmentioning
confidence: 99%